2013
DOI: 10.1371/journal.pone.0076562
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Neurobehavioral, Social, and Emotional Dysfunction in Patients Treated for Childhood Craniopharyngioma: A Systematic Literature Review

Abstract: BackgroundCraniopharyngiomas (CP) are locally invasive and frequently recurring neoplasms often resulting in neurological and endocrinological dysfunction in children. In addition, social-behavioral impairment is commonly reported following treatment for childhood CP, yet remains to be fully understood. The authors aimed to further characterize the prevalence of neurobehavioral, social, and emotional dysfunction in survivors of childhood craniopharyngiomas.Materials and MethodsA systematic literature review wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
68
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(69 citation statements)
references
References 40 publications
0
68
1
Order By: Relevance
“…Several studies have shown dramatic reductions in memory, executive functions, and QOL in pediatric patients with craniopharyngiomas, particularly those with hypothalamic involvement, with as many as 57% showing neurobehavioral dysfunction. 46 Three prior studies have examined QOL in adult patients. The more recent study included 29 cured adults with 19 years of follow-up and compared results of 4 health-related questionnaires with those administered to 142 matched controls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown dramatic reductions in memory, executive functions, and QOL in pediatric patients with craniopharyngiomas, particularly those with hypothalamic involvement, with as many as 57% showing neurobehavioral dysfunction. 46 Three prior studies have examined QOL in adult patients. The more recent study included 29 cured adults with 19 years of follow-up and compared results of 4 health-related questionnaires with those administered to 142 matched controls.…”
Section: Discussionmentioning
confidence: 99%
“…At time of presentation, and certainly after treatment, craniopharyngiomas can be associated with visual field defects, endocrinopathies, hypothalamic syndromes, increased cardiovascular risk, and neurocognitive sequelae. 7,9,33,37,46 Although considered benign tumors, their location can impact critical structures such as the optic nerves and chiasm, hypoabbreviatioNs ASBQ = Anterior Skull Base Quality of Life; BMI = body mass index; GTR = gross-total resection; QOL = quality of life; obJect Craniopharyngiomas are benign parasellar tumors for which surgical removal, although potentially curative, often leads to morbidity with resulting decreases in quality of life (QOL). The endonasal endoscopic approach is a minimal-access technique for removing these tumors and may reduce postoperative morbidity.…”
mentioning
confidence: 99%
“…Neurocognitive and neurobehavioral dysfunctions are still among the primary concerns for complications in survivors of childhood craniopharyngioma (31)(32)(33)(34). Previous studies have reported that post-therapeutic cognitive and behavioral outcomes were implicated by normal brain volume receiving a high radiation dose and various surgical factors such as CSF shunting, presence of ommaya reservoir, and extent of resection (32,33).…”
Section: Effect Of Surgical Defects and Implicationsmentioning
confidence: 99%
“…1,44 The lesion is histologically benign but, due to its proximity to the critical neurovascular and hypothalamopituitary axis structures, it poses challenges to the treating physician. 1,61 Surgical or adjuvant treatment strategies in this eloquent location may have devastating effects, especially in the pediatric population in whom hypothalamic injury can result in the development of morbid obesity and cognitive decline. 21 Almost all pediatric craniopharyngiomas are of the adamantinomatous type with a CTNNB1 mutation, and they are generally calcified and thus not only more difficult to resect but also not responsive to medical therapy.…”
mentioning
confidence: 99%